Fracture Characteristics of Mélange Complex Basement in Bantimala Area, South Sulawesi, Indonesia - Benyamin Sapiie; Muhamad Aziz Nugraha; Rizky Kurniawan Wardana; Arif Rifiyanto (Geological Agency, 2017)
DOI: 10.17014/ijog.4.3.121-141A detailed geological mapping and fracture characterization had been performed in Bantimala area, South Sulawesi, Indonesia. The geology of the studied area is composed of pre-Tertiary metamorphic, sedimentary, and igneous rocks which tectonically mixed forming a mélange complex. Located on the southeastern margin of Sundaland, the tectonic strongly influences the fracture occurrences in the studied area. A total of 3,841 fractures comprising shear fractures, extension fractures, veins, and joints have been measured and analyzed. The common fracture orientations are NW - SE, W - E, NNE - SSW, and ENE - WSW trends. Fractures developing in Bantimala have clearly been controlled by lithology and structure position (i.e. fault zones and fold hinge). The orientation of fractures in Bantimala area is different on each lithology, showing that the fracture system was complex. Fracture intensity in schist is higher compared to the other lithologies. The 3D fracture modeling through 3D geocellular modeling was generated using the result from field data measurements and analyses. Discrete Fracture Network (DFN) was built by fifty-one fracture sets that were analyzed from field measurement data. However, the estimation of average fracture porosity from modeling varies significantly depending on lithology. The value of fracture porosity is relatively small, varied from 0.0004 to 0.0029 %. A high fracture porosity number is observed in an area with a significant fracture intensity and most crosscutting of fracture which in turn is controlled by faults and lithology. A mélange complex can have high potential as a basement fractured reservoir target, where fracture distributions and their attributes will vary depending on the lithology as well as local deformation.